FPGA Implementation of Automatic Irrigation and Pesticide Control System - D. Hanitha; B. Anusha; M. Durga Prakash (International Journal of Reconfigurable and Embedded Systems (IJRES), 2016)
In many parts of the world rainfalls are inadequate to meet agricultural needs of farmers. It thus becomes imperative to use an irrigation system that meets the moisture needs of plants in order to increase food crop production. The system described here monitors the moisture and pesticide control needs of crops. Irrigation control is monitored through suitable moisture sensors and automatically pumps water when the need arises through FPGA control logic thus requiring minimal human interventions. We can also use this system for liquid pesticide supply through the selection. Thus, we achieve the efficient supply of water and pesticide as needed by plants and conserve quantity, energy and time. In this paper, the proposed system is designed using Verilog and implemented on FPGA. The system operation is also explained in DSCH (Digital Schematic) software. The system is very simple to operate and ideally suits the irrigation and pesticide need for green houses as well as farms.